Pendekatan Saintifik dalam Pembelajaran Pendidikan Agama Buddha dan Budi Pekerti - Hadion Wijoyo (STAB Maitreyawira, 2025)
The scientific approach in Buddhism and Ethics Education for literature explanation is still lacking. In fact, the approach is important to be understood by Buddhist Education and Budi Pekerti teachers. Therefore, research will be made on the Scientific Approach in Learning Buddhist Education and Budi Pekerti. This research uses a qualitative method with the type of literature study. Literature study research is the result of research that makes theoretical studies as the basis for its discussion. Therefore, the theory in literature study research must be complete so that the results of the research are also complete. The time in this research is from January to March 2025. For the research data validity testing plan, namely using the credibility test, dependability test, and conformity test. Based on the results of the study, the scientific approach has many advantages that are very beneficial for student development in terms of knowledge, attitudes, and skills in learning Buddhist Religious Education and Budi Pekerti. The scientific approach is an idea (at the philosophical level) to achieve goals that can be implemented by anyone. The scientific approach can be implemented by every Buddhist Religious Education and Budi Pekerti teacher to achieve learning objectives. Furthermore. Learning activities carried out through the Scientific Method are through the process of observing, questioning, trying, reasoning, and communicating.